The Memory Effect of Reflected Self-Appraisals on Different Types of Others - Yue, Caizhen; Yang, Yajun; He, Weijie; Yue, Tong; Pan, Weigang (Frontiers in Psychology, 2020)
The development of one’s self-concept unfolds within early interactions with intimate significant others for childhood and adolescence. Previous studies suggest that people define themselves in part through internalized perceptions of other people’s beliefs about them, known as reflected self-appraisals. Even in adulthood, reflected self-appraisals still remain critically influential on direct self-appraisals, and the affect might depend on the different types of others. In the present study, for the first time, we extend the classic “other-reference” paradigm to the field of reflected self-appraisals in order to examine whether there is a difference in the memory performance of reflected self-appraisals on different types of others in an early adult sample. In the experiment, participants were told to encode personality trait words by judging how different types of others (romantic partners, friends, and classmates) think about the participants themselves. After a retention interval, they received a surprise recognition memory test. The results showed that the memory performance of romantic partners is significantly better than that of friends and classmates, indicating that the memory performance of reflected self-appraisals varies across the others with different levels of closeness. Specifically, the closer the relationship between people and others is, the better the memory performance of reflected self-appraisals will be. Meanwhile, the speed and the encoding deepness of the reflected self-appraisals vary among different genders, leading to the gender effect of recognition memory. This study might help deepen our understanding on the development of self-concept in adulthood.